The functional comparative method: a way to teach grammar - Velázquez Avila, Kenia María; Santiesteban Naranjo, Ernan (Didáctica. Lengua y Literatura, 2019)
The social communicator must possess a communicative competence; however, through the application of research methods, it was found that they present inadequacies that limit the processes of professional communication. One of the causes that generates this contradiction is the insufficient argumentation of the didactic methods. In order to corroborate the above, a diachronic study of the teaching-learning process of Grammar was carried out, and from the limitations found in didactic theories the functional comparative method is proposed. It also describes each of the actions carried out during the experimental period. It is significant to note that the results presented are part of the research project: The Teaching of Grammar in Higher Education, University of Las Tunas, Cuba. This project is associated to the Ibero-American Network of Pedagogy in which it is tried to implement the proposed method in several universities of Latin America.